A little light : stories - Mohlele, Nthikeng (2023)
""The world may be full of women of varying beauty and talents, but I doubt there will ever be an encounter like this one, so charged, so urgent and, like I said, beautifully irrational." - In Praise of Older Women. A new collection of stories by of South Africa's most original writers, A Little Light is a timely and sensitive evocation of places, bodies, politics, regrets and hope, all revealed in tightly controlled and beautifully lit stories. Mohlele's daring writing is on full display with the publication of this volume. Nthikeng Mohlele was partly raised in Limpopo and Tembisa Township, and attended the University of the Witwatersrand, where he obtained a BA in dramatic art, publishing studies and African literature. He is the author of six critically acclaimed novels: The Scent of Bliss (2008), Small Things (2013), Rusty Bell (2014), Pleasure (2016), Michael K (2018), Illumination (2019) and a short-story collection, The Discovery of Love (2021). Nthikeng was the winner of the University of Johannesburg Prize for South African Writing in English, winner of the K. Sello Duiker Memorial Award, winner of the National Institute for the Humanities and Social Sciences Award for Best Fiction: Short Stories and was long-listed for the International Dublin Literary Award." --Publisher's description.
Keywords: Short stories, South African (English); South African fiction (English)